Phytohormones as important biologically active molecules--their simple simultaneous detection - Diopan, Vaclav; Adam, Vojtech; Havel, Ladislav; Kizek, Rene (Molecules (Basel, Switzerland), 2009)
Phytohormones, their functions, synthesis and effects, are of great interest. To study them in plant tissues accurate and sensitive methods are required. In the present study we aimed at optimizing experimental conditions to separate and determine not only plant hormones but also their metabolites, by liquid chromatography coupled with a UV-VIS detector. The mixture we analyzed was composed of benzyladenine, kinetin, trans-zeatin, cis-zeatin, dihydrozeatin, meta-topolin, ortho-topolin, alpha-naphthalene acetic acid, indole-3-acetic acid, trans-zeatin-7-glucoside, trans-zeatin-O-glucoside, trans-zeatin-9-riboside, meta-topolin-9-riboside and ortho-topolin-9-riboside. We measured the calibration dependences and estimated limits of detection and quantification under the optimal chromatographic conditions (column: Polaris C(18); mobile phase: gradient starting at 2:98 (methanol:0.001% TFA) and was increasing to 55:45 during twenty minutes, and then decreasing for 10 min to 35:65, flow rate: 200 microL x min(-1), temperature: 50 degrees C, wavelength: 210 nm). The detection limits for the target molecules were estimated as tens of ng per mL. We also studied the effect of flax extracts on the phytohormones' signals. Recovery of aliphatic and aromatic cytokinins, metabolites of cytokinins and auxins were within the range from 87 to 105 %. The experimental conditions were tested on a mass selective detector. In addition we analysed a commercial product used for stimulation of roots formation in cuttings of poorly rooting plants. The determined content of alpha-naphthalene acetic acid was in good agreement with that declared by the manufacturer.
Keywords: Trifluoroacetic Acid; Cytokinins; cytokininy; molekulární struktura; regulátory růstu rostlin; Plant Growth Regulators; Spectrophotometry, Ultraviolet; spektrofotometrie ultrafialová; Chromatography, Liquid; chromatografie kapalinová; kyselina trifluoroctová; Molecular Structure